38 Plasma proteomic signature of motoric cognitive risk syndrome - Gomez, Gabriela T.; Sathyan, Sanish; Chen, Jingsha; Fornage, Myriam; Schlosser, Pascal; Peng, Zhongsheng; Cordon, Jenifer; Palta, Priya; Sullivan, Kevin J.; Tin, Adrienne; Windham, B. Gwen; Gottesman, Rebecca F.; et al. (Journal of clinical and translational science, 2023)
OBJECTIVES/GOALS: Motoric cognitive risk (MCR) is a pre-dementia syndrome characterized by slow gait and subjective cognitive complaints. In the Atherosclerosis Risk in Communities (ARIC) study, we aim to (1) identify plasma proteins and protein modules associated with MCR and (2) compare the proteomic signature of MCR to that of mild cognitive impairment (MCI). METHODS/STUDY POPULATION: Nondemented ARIC participants were classified by MCR status (yes/no) according to a memory questionnaire and 4-meter walk. MCI status (yes/no) was classified by expert diagnosis using standardized criteria. We measured 4,877 proteins in plasma collected at ARIC Visit 5 (late-life) and Visit 2 (midlife) utilizing the SomaScan4 proteomic assay. Multivariable logistic regression”adjusted for demographic variables, kidney function, cardiovascular risk factors, and APOE4 status”related each protein to MCR at late-life. An FDR corrected P RESULTS/ANTICIPATED RESULTS: Proteome-wide association study among 4076 ARIC participants (mean age=75; 58% women, 17% Black, 4% MCR+, 21% MCI+; MCR+ and MCI+ groups overlapped) at late-life identified 26 MCR-associated proteins involved in metabolism, vascular/visceral smooth muscle, and extracellular matrix organization. At an uncorrected P DISCUSSION/SIGNIFICANCE: This proteomic characterization of MCR identifies novel plasma proteins and networks, both distinct from and overlapping with those of MCI, thus highlighting the partially divergent mechanisms underlying these pre-dementia syndromes. These findings may be leveraged toward dementia prognostication and targeted therapeutic approaches.